D* production in deep inelastic scattering at HERA - Breitweg, J; Derrick, M; Krakauer, D; Magill, S; Mikunas, D; Musgrave, B; Repond, J; Stanek, R; Talaga, R; Yoshida, R; Zhang, H; Mattingly, M; et al. (1997)
This paper presents measurements of D*f± production in deep inelastic scattering from collisions between 27.5GeV positrons and 820GeV protons. The data have been taken with the ZEUS detector at HERA. The decay channel D*+ → (D0 → K-π+)π+ (+c.c.) has been used in the study. The e+p cross section for inclusive D*± production with 5 < Q2 < 100GeV2 and y < 0.7 is 5.3±1.0±0.8nb in the kinematic region 1.3 < pT(D*±) < 9.0GeV and |η(D*±) | < 1.5. Differential cross sections as functions of pT(D*±), η(D*±), W and Q2 are compared with next-to-leading order QCD calculations based on the photon-gluon fusion production mechanism. After an extrapolation of the cross section to the full kinematic region in pT(D*±) and η(D*±), the charm contribution Fcc̄2(x,Q2) to the proton structure function is determined for Bjorken x between 2 · 10-4 and 5 · 10-3. © 1997 Elsevier Science B.V.